MORADIA, RISCOS URBANOS E MEIO AMBIENTE SUSTENTÁVEL: SUSTENTÁCULOS E FATORES PERCUCIENTES A UMA IGUALITÁRIA CONSTITUCIONALIZAÇÃO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2012)
This study seeks to identify and analyze the occurrence of environmental and social effects and mutations, as contemporaneity triggers the occurrence of risks, including urban ones. The pursuit of constitutional rights to the environment and to housing are a definite problem, pressing for legal action and constitutional effectiveness, in a modern scenario lacking ways capable of guaranteeing the concreteness of existential conditions, less and less experienced, behold, under the threatening aegis of future damage and imminent risks. Treating the theme of society, especially in contemporary auspices, therefore implies an overriding analysis of historicity to the present day, having as a basic source a theory that discusses the social transformations and evolutions that have occurred in time. Similarly, there is an urgent need to analyze these transformations in a way that supports the visualization and confrontation of the social phenomena under which the current world lives, and with regard specifically to sustainable environmental development, the social and environmental function of housing and the exercise of the right to housing in the face of the development of urban risks, in our dynamic today. In this sense, the present article proposes the study about the fundamentality and the justiciality of the rights to the environment and housing, in order that we make efforts to guarantee a humanitarian, social and legal system. To this end, a theoretical-qualitative rescue on the theme will be carried out, drawing perspectives for a constitutional order that perpetuates an amplified democracy as a factor of perpetuation of fundamental rights in an equitable way.